Comparative Structural Evaluation of Transit Travel Demand using Travel Survey and Smart Card Data for Metropolitan Transit Financing. Issue 8 (December 2018) - Spurr, Tim; Leroux, Antoine; Chapleau, Robert
Lrge metropolitan areas often comprise multiple municipalities and multiple transit-operating agencies that share infrastructure and passengers. In such cases, financing mechanisms are devised to share costs and revenues among the various jurisdictions. Using Montréal, Canada, as a case study, this paper investigates whether a large sample household travel survey (HTS) can provide sufficiently accurate and detailed information to form the basis for a metropolitan transit financing framework. The evaluation is made possible by the existence of a smart card (SC) fare collection system, deployed across the region, which provides, with some processing, an independent source of transit trip information. The structure of transit travel demand, as measured by SC and the HTS, were compared. The structural elements examined included the types of fare product used, the temporal distribution of trips during a typical weekday, and the spatial and temporal distribution of trips over the multiple networks serving the metropolitan area. The results of the comparison showed that the HTS constitutes a simplified portrayal of transit demand that over-represents symmetrical travel patterns prevalent during peak periods and under-represents other travel patterns. An important consequence of this bias is the over-representation of travel between the suburbs and downtown. Two theoretical allocation scenarios were designed to evaluate the potential effects of these differences on metropolitan-level cost- and revenue-sharing. A simple experiment showed the effects to be significant.